2022
DOI: 10.3390/buildings12101509
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Adoption of Modular Construction in Portugal: An Interpretive Structural Modeling Approach

Abstract: Modular construction is the most advanced method of off-site construction available, generating fully-fitted modules with up to 80% of the work completed in a controlled environment prior to their transportation and installation on-site. The adoption of modular construction (AMC) has increased in several countries worldwide. However, in smaller construction markets, the adoption rates remain low, and the industry is still heavily reliant on traditional labor-intensive methods. The main research question for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…It was found that prefabrication and modularization offer numerous advantages, such as flexibility in design and the ability to customize and standardize constructive elements. However, Ribeiro et al [79] identified specific barriers associated with prefabrication. One such barrier is that architectural design often fails to consider the modular construction aspect, primarily due to aesthetic limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that prefabrication and modularization offer numerous advantages, such as flexibility in design and the ability to customize and standardize constructive elements. However, Ribeiro et al [79] identified specific barriers associated with prefabrication. One such barrier is that architectural design often fails to consider the modular construction aspect, primarily due to aesthetic limitations.…”
Section: Discussionmentioning
confidence: 99%
“…With a path coefficient of 0.56, the attitudinal barriers are placed first and regarded as the most important barrier among the other variables that influence the adoption of PC in residential developments. Prior studies in numerous nations identified and discussed the attitudinal barriers (Ali et al, 2023;Hwang et al, 2018;Ribeiro et al, 2022) , so this issue should be made clear in order to increase PC in residential projects. There is a relatively low level of research and development on prefabrication construction in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The number of experts and specialists fluctuates in accordance with the specific investigation being conducted, presenting a considerable degree of variation, as evidenced by the range typically falling within the parameters of 5 to 15 individuals (Goyal and Kumar, 2017;Ribeiro et al, 2022;Kaur et al, 2023). In this study, seven participants were involved in focus group sessions of approximately one to one and a half hours.…”
Section: Methodsmentioning
confidence: 95%